Palladium-Catalyzed Coupling Reactions on Functionalized 2-Trifluoromethyl-4-chromenone Scaffolds: Synthesis of Highly Functionalized Trifluoromethyl Heterocycles - Izquierdo, Javier; Jain, Atul D.; Abdulkadir, Sarki A.; Schiltz, Gary E. (Synthesis, 2019)
The chromenone core is an ubiquitous group in biologically active natural products and has been extensively used in organic synthesis. Fluorine-derived compounds, including those with a trifluoromethyl group (CF3), have shown enhanced biological activities in numerous pharmaceuticals compared with their non-fluorinated analogues. 2-Trifluoromethylchromenones can be readily functionalized at the 8- and 7-positions, providing chromenones cores of high structural complexity, which are excellent precursors for numerous trifluoromethyl heterocycles.
Keywords: fluorine; chromenone; trifluoromethyl heterocycle synthesis; palladium-catalyzed coupling